Body mass index changes in children and adolescents with intelectual disability during the COVID-19 pandemic - Nika Šuc; Blaž Lešnik (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2022)
Introduction: Intellectual disability (ID) is a generalized neurodevelopmental disorder characterized by significantly impaired intellectual and adaptive functioning. Body mass index (BMI) is a value derived from the mass (weight) and height of a person. Due to the COVID-19 pandemic there was a lockdown of all schools and other daily sport activities. Methods: We measured the height and weight of 100 children and adolescents with intellectual disability. The measurements were taken in September 2020 and then six months later, in March 2021. The calculated BMI was transformed into age- and sex-standardized values (zBMI). Mean BMI and zBMI were compared over time and between sexes using a paired t-test and two-way mixed analysis of variance (ANOVA). The effect size was estimated using Cohen's d. Results: On average across all groups, BMI increased by 0.5kg/m2 in the studied period. The increase in mean BMI was statistically significant for both groups of girls; the difference between girls and boys in BMI increase was marginally statistically significant. The analysis of zBMI confirmed that the observed changes were likely not simply a consequence of maturation. Discussion: One effect of the COVID-19 pandemic and restrictions related to it was the increase of BMI values in children and youth. With our results, we can relate this data also to population with ID. Although we have provided intervention programs and encouraged pupils and their parents to be more physically active during lockdown, the importance of school and after school activities regarding physical fitness status is clearly evident.